2016
DOI: 10.1002/smll.201602902
|View full text |Cite
|
Sign up to set email alerts
|

Electrohydrodynamic‐Induced SERS Immunoassay for Extensive Multiplexed Biomarker Sensing

Abstract: Cancer diagnosis and patient monitoring require sensitive and simultaneous measurement of multiple cancer biomarkers considering that single biomarker analysis present inadequate information on the underlying biological transformations. Thus, development of sensitive and selective assays for multiple biomarker detection might improve clinical diagnosis and expedite the treatment process. Herein, a microfluidic platform for the rapid, sensitive, and parallel detection of multiple cancer-specific protein biomark… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
35
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 83 publications
(37 citation statements)
references
References 49 publications
0
35
0
Order By: Relevance
“…The SERS nanotags were prepared by the same method as described by our previous studies(Kamil Reza et al 2016). The gold nanoparticles were synthesized by citrate reduction of HAuCl4 as reported in literature.…”
Section: Preparation Of Sers Nanotagsmentioning
confidence: 99%
See 1 more Smart Citation
“…The SERS nanotags were prepared by the same method as described by our previous studies(Kamil Reza et al 2016). The gold nanoparticles were synthesized by citrate reduction of HAuCl4 as reported in literature.…”
Section: Preparation Of Sers Nanotagsmentioning
confidence: 99%
“…To address this limitation, we have recently developed a SERS-microfluidic platform which utilizes alternating current electrohydrodynamic (ac-EHD) fluid flow thus avoiding the use of any external pump. This ac-EHD induced fluid flow generates a nanoscale shear force at the double layer of the sensing electrodes which significantly increases the antibody-target binding and at the same time shears off the non-specifically bound molecules from the sensor surface (Kamil Reza et al 2016;Wang et al 2015). Despite this advantages, this method utilized biotin-streptavidin chemistry followed by immune-affinity approach using monoclonal antibody which limits its application in clinical settings.…”
Section: Introductionmentioning
confidence: 99%
“…This study demonstrated that the proposed platform was highly sensitive (10 fg/mL) and had great potential to detect protein biomarkers in patient samples. This platform was further developed to simultaneously detect multiple cancer protein biomarkers from clinical samples by using 4 different SERS nanotags [96]. They constructed a microfluidic device containing five individual microchannels with each channel comprehending an array of asymmetric electrode pairs (Fig.…”
Section: Protein Biomarkersmentioning
confidence: 99%
“…Cited from Ref. [126], [95], [96] and [99] immunoassay method using electrohydrodynamic (ac-EHD) force to markedly reduce the assay time and nonspecific binding for breast cancer biomarkers detection (Fig. 3B) [95].…”
Section: Protein Biomarkersmentioning
confidence: 99%
“…154 There is also ample evidence suggesting that a panel of protein biomarkers provide more information than a single one for clinical diagnosis, 155,156 [163][164][165][166][167] and (iv) microfluidic immunoassays. [168][169][170][171] The captured proteins are then detected based on either the "fingerprint" information of target proteins 172,173 or the characteristic spectra of Raman reporters conjugated to plasmonic nanomaterials. 41,61,[157][158][159][160][161][162][163][164][165][166][168][169][170][171][174][175][176][177][178] Although both SERS read-out methods can provide sensitive and specific detection of circulating target proteins, nanotag-based SERS immunoassays are more commonly used due to the availability of direct multiplex readouts based on unique spectral signals and strong signals provided by the Raman reporters with large SERS cross sections.…”
Section: Circulating Cancer Protein Biomarkersmentioning
confidence: 99%